Analgesic Effect of Zanthoxylum nitidum Extract in Inflammatory Pain Models Through Targeting of ERK and NF-κB Signaling - Qin, Fenfen; Zhang, Han; Liu, Anlong; Wang, Qisheng; Sun, Qinmei; Lu, Shengfeng; Li, Qian; Guo, Hongwei; Liu, Xing; Lu, Zhigang (Frontiers in Pharmacology, 2019)
Background: Zanthoxylum nitidum (Roxb.) DC., also named Liang Mianzhen (LMZ), one kind of chinese herb characterized with anti-inflammatory and relieving pain, which is widely used to treat injuries, rheumatism, arthralgia, stomach pain and so on in China. But its mechanisms related to the anti-hyperalgesic has not been reported. The aim of the present study was to investigate the analgesic activity of LMZ on mice with Complete Freund adjuvant(CFA)-induced chronic inflammatory pain. Meanwhile, the peripheral and central mechanisms of analgesic effect of LMZ were further examined via observing the effects of LMZ on the signal pathway associated with inflammatory induced hyperalgesia. Methods: The inflammatory pain model was established by intraplantar injection of CFA in C57BL/6J mice. After 1 day of CFA injection, the mice were treated with LMZ(100mg/kg) for 7 consecutive days, and the behavioral tests were measured after the daily intragastric administration. The morphological changes on inflamed paw sections were determined for hematoxylin-eosin(HE) staining. Changes of TNF-α, IL-1β, IL-6 and NF-κBp65 in the mRNA expression and protein quantity were measured on day 7 after CFA injection by the real-time quantitative PCR analysis and ELISA method, respectively. Moreover, immunohistochemistry and western blotting were used to detect ERK1/2 and NF-κB signal pathway activation. Results: The extract of LMZ(100mg/kg) showed a significant anti-inflammatory and analgesic effect in these mice. The paw edema volume was significantly reduced after administration with LMZ compared to CFA group, as well as the paw tissues inflammatory damage was relived and the numbers of neutrophils in mice was reduced significantly. The CFA-induced mechanical threshold and thermal hyperalgesia value were significant improved with LMZ treatment at day 3 to day 7. We also found the mRNA and protein levels of TNF-α, IL-1β, IL-6 and NF-κBp65 were respectively down-regulate after 7 days LMZ treatment compared to CFA group. Meanwhile, LMZ significantly suppressed over-expression of the phosphorylation of ERK1/2 and NF-κBp65 in peripheral and central. Conclusions: The present study suggests that the extract of LMZ attenuates CFA-induced inflammatory pain by suppressing the ERK1/2 and NF-κB signalling pathway at both peripheral and central level.